2016
DOI: 10.2308/jeta-51477
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretive Structural Modeling Approach to Analyze the Interaction between Factors of the Fair Value Measurement Audit Process

Abstract: Fair value measurements (FVM) have now emerged as an integral part of accounting and auditing standards. Many countries across the globe have initiated FVM-based standards and others are in the process of their adoption. The FVM audit process is, nevertheless, a tedious job for auditors, mainly because of the influence of numerous direct or indirect factors in the audit process and its outcome. A major issue for auditors is to identify and understand the complexity of these factors for a FVM audit. To the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The auditors face difficulty in auditing the fair value estimates due to estimation uncertainty and lack of reliable information. They rely on managerial estimates for determining fair values (Abdullatif, 2016; Doliya & Singh, 2016). Thus, in the context of FVA, the auditors’ report assumes special and extra significance, since auditors would, in general, not be expected to compromise on reliability of the information.…”
Section: Resultsmentioning
confidence: 99%
“…The auditors face difficulty in auditing the fair value estimates due to estimation uncertainty and lack of reliable information. They rely on managerial estimates for determining fair values (Abdullatif, 2016; Doliya & Singh, 2016). Thus, in the context of FVA, the auditors’ report assumes special and extra significance, since auditors would, in general, not be expected to compromise on reliability of the information.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies showed that earnings management practices increase the potential litigation risk and lead to higher AF (Abbott et al , 2006; Barron et al , 2001). Also, fair value under OCI increases the burden on auditors and require professional knowledge (Martin et al , 2006; Doliya and Singh, 2016), and it is difficult for auditors to obtain specialized valuation knowledge to effectively audit FV of certain financial assets and liabilities (Martin et al , 2006). Besides, OCI may require more audit effort as the investors react greatly to the OCI volatility.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Also, auditing the OCI may increase the audit effort to lower the detection risk. Moreover, auditors may find difficulties when auditing the FV under OCI and need professional knowledge (Doliya and Singh, 2016; Martin et al , 2006); in this line, the Egyptian Auditing Standard No (545): “a review of fair value measurement and disclosure” indicates that FV measurements are complex in nature and are characterized by a high degree of uncertainty (Egyptian Auditing Standards, 2008). Therefore, the auditor’s understanding of the FV measurement process and its complexity help him in identifying and assessing the risks of significant misstatement, to determine the nature, timing and extent of additional audit procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Specific literature has identified several influential factors in the FV estimation audit, those often cited and transposed here in our own words being 'Fair value complexity', 'Estimation uncertainty', 'Managerial bias', 'Professional skepticism', 'Fair value estimate provider', 'Standards guidance', and 'Auditors understanding of the valuation process' (e.g. Bratten et al, 2013 or Doliya andSingh, 2016).…”
Section: Influential Factors For Fv Estimation and Induced Audit Risksmentioning
confidence: 99%